# Yahoo Web Search

related to: cbs

1. ### For the equation, cb + cx = a - cx , solve for x?

cb + cx = a - cx cb + cx + cx = a cx + cx = a - cb 2cx = a - cb x = (a - cb ) / 2c

5 Answers · Science & Mathematics · 23/01/2013

2. ### how do you find CB , AB, AD, CD, and AC?

Given that DB=2, we will first find CB using cos 60 = DB/BC which is... = AD+DB = 6+2= 8. Recap CB =4 AB=8 AD=6 CD=2*sqrt(3) ...

2 Answers · Science & Mathematics · 12/09/2007

3. ### Math help...Convert the hexadecimal numeral CB to a binary numeral.?

... adding 192 + 11 we find it is 203 base 10. To change CB directly to base 2 or Binary is much easier because 16 is...

3 Answers · Science & Mathematics · 18/12/2008

4. ### the triangle ABC has CA= CB .?

...foot of the perpendicular from C to PA. Since arc(CA) = arc( CB ), angle(CPA) = angle(CPB), the latter implies ΔCPE...

1 Answers · Science & Mathematics · 22/08/2009

5. ### solve the triangle for side CB .....?

........_________________ c = √a^2 + b^2 - 2ab cosx ........_________________________ CB = √42^2 + 21^2 - 2(42)(21) cos 39 ........____________________ CB = √1764 + 441 - 1764cos39...

1 Answers · Science & Mathematics · 10/12/2009

6. ### Find the value of the constants C and b so that the curve y = Cb ^x contains (2,3) and (3,9)?

Y= Cb ^x) Y2=9, Y1=3; X2=3; X1=2 (Y2-...

1 Answers · Science & Mathematics · 19/04/2013

7. ### show that (a + cb , b) = (a, b)?

...above expression means. Anyway, on to the proof. Let d = (a + cb , b) and d' = (a, b). We note that d' | a and d' | b, so d'...

4 Answers · Science & Mathematics · 27/07/2008

8. ### GCD Proof (a,b) = (a+ cb ,b)?

... coprimes so there exists x and y so that gx + dy = 1 now a + cb = fd +cfg = f(d + gc) as gx + dy =1 add and subtract gcy on LHS gx -gcy + dy...

3 Answers · Science & Mathematics · 12/09/2011

9. ### If AC = 12 cm and CB = 16 cm, what is the length AB?

Since ABC is a right triangle, AC^2 + CB ^2 = AB^2 12^2 + 16^2 = 144 + 256 = 400. 400 = 20^2 AB = 20 cm...

5 Answers · Science & Mathematics · 02/08/2013

10. ### find the value of t when AB = CB ?

When AB= CB a+tb = a+(3t-5)b .... add ( -a) to both sides , gives tb = (3t - 5)b ....... divide both sides by "b" gives t = 3t - 5 5 = 2t t = 5/2

2 Answers · Science & Mathematics · 23/04/2013